Cardiac Imaging in Patients With Ventricular Tachycardia. Issue 25 (19th December 2017) - Mahida, Saagar; Sacher, Frédéric; Dubois, Rémi; Sermesant, Maxime; Bogun, Frank; Haïssaguerre, Michel; Jaïs, Pierre; Cochet, Hubert
Abstract : Ventricular tachycardia (VT) is a major cause of sudden cardiac death. The majority of malignant VTs occur in patients with structural heart disease. Multimodality imaging techniques play an integral role in determining the underlying etiology and prognostic significance of VT. In recent years, advances in imaging technology have enabled characterization of the structural arrhythmogenic substrate in patients with VT with increasing precision. In parallel with these advances, the role of cardiac imaging has expanded from a largely diagnostic tool to an adjunctive tool to guide interventional approaches for treatment of VT. Invasive and noninvasive imaging techniques, often used in combination, have made it possible to integrate structural and electrophysiological information during VT ablation procedures. An important area of current development is the use of noninvasive imaging techniques based on body surface electrocardiographic mapping to elucidate the mechanisms of VT. In the future, these techniques may provide a priori information on mechanisms of VT in patients undergoing interventional procedures. This review provides an overview of the role of cardiac imaging in patients with VT. Abstract : Supplemental Digital Content is available in the text.